Djava Dvipa Boardgame - Nugroho, Listyanto Aji (Universitas Negeri Semarang, 2024)
The objective of this study is to create a gamified history learning tool that delves into students' comprehension of the grand kingdoms of the Nusantara, sparks their interest in learning, and encourages exploration of the cultural heritage of the Nusantara. The research employed the ADDIE development model as its methodology. The outcome of this investigation is the